(untitled) (Bulletin KNOB, 1991)
J.G. Michael, who served the Prince of Waldeck at Residenz Arolsen as Hofgärtner from 1740 to 1778, taught his son Johann Georg Michael (1738-1800) the trade of gardener. Jacob Boreel Jansz., owner of the Dutch country seat Beeckesteyn at Velsen, kept up commercial relations with the principality of Waldeck-Pyrmont. In the early sixties of the 18th century he brought young Johann Georg Michael from Arolsen to Beeckesteyn to work for him on his country seat. As envoy extraordinary at the English court (1761-62) Boreel recommended Michael to go to England to study the lay-out of English parks. After Boreel’s departure in 1778 Michael probably stayed in the family’s service, but he was enabled to accept other commissions as well, such as the alterations of the country seats Elswout and Waterland’s gardens or the reorganization of the Kurpark of Pyrmont. In his absence activities in the Netherlands were taken over by his prospective son-in-law J.D. Zocher. Sr. Michael’s activities between 1765 and 1800 coincide with the period of Neo-Classicism. Three aspects must have been important at the creation of his interpretation of the English and/or Chinese landscape style. First of all his journey to England, where he studied the landscape style as practiced by Lancelot Brown (1716-1783) and the neo-classical and Neo-Gothic architecture in these parks. Then, contemporary manuals on the new natural style like Designs of Chinese buildings by W. Chambers (Dutch translation 1763), Stowe, a description of the magnificent house and gardens, London 1769 (with plans and pictures) and Observations on modern gardening by Th. Whately (German translation 1771). Thirdly, his possible acquaintance with other Dutch parks, which had been transformed into the natural style in an early phase, Michael certainly adapted Chambers’ characteristics like scenes with much variation, wherein water (cascades) and mountains (difference in levels) play an important role. J.G. Michael also knew the book on Stowe, one of the first English parks wherein from 1730 on, the free natural style was adapted by Charles Bridgeman, William Kent and Lancelot Brown successively. He most probably made a journey to England and visited the park of Stowe. The similarity in architecture and the Corinthian Arch on Stowe and the colonnade on Beeckesteyn are indications. Thomas Whately discusses in his Observations on modern gardening the English landscape style as adapted by Lancelot Brown. At Whately the layout with a romantic character starts to shift to a lay-out with a rural, agricultural character. Michael mainly adopted Whately’s ’materials’. The landscape style as adapted hereafter in France, Germany and the Netherlands mingles characteristic elements of the Chinese and English style. Therefore in France one speaks of the Anglo-Chinese style. Up to the present twelve of Michael’s later designs are known, but the number of projects is much larger. Most of these projects are situated in Dutch South-Kennemerland and Gelderland and were created between 1772 and 1795. Analysis of form defines maintenance of a part of the sight avenue, situated behind an open space behind the house as Michael’s signature. Incidentally the axe is finished by a garden ornament. Walks are laid out along paths with varying sights. Ponds are laid out in natural forms. Architecture is built in the neo-classical, neo-gothic and Chinese style. A farm or stable can strengthen the agricultural character. The book of reproductions Recueil des jardins anglo-chinois by G.L. Le Rouge (Paris 1775-1788) with many examples of Chinese architecture must have been an important source of inspiration. Michael’s conceptions have been fed by the Chinese art of landscape gardening, described by W. Chambers and the early English landscape style of Lancelot Brown, theoretically worked out by Th. Whately. The theories of Chambers and Whately, grounded on the practice in China and England and amplified with those of Watelet and Walpole, were summed up by C.C.L. Hirschfeld in his Theorie der Gartenkunst, Leipzig, 1779-1785, 5 Vol. This Standard work was very important to the spread of the English-Chinese landscape style in Western Europe and must have been known to Michael. As far as we know he has not been influenced by colleague landscape gardeners in the Netherlands.